Analysis of professional competency awareness based on visible network graphs - Meng, Shilin; Han, Lidan; Mou, Pengbing (Frontiers in Physics, 2024)
With the development of society and technological advancement, the focus on professional competency has gradually increased. This paper conducts an in-depth analysis of the Baidu search index for "professional competency" from July 3, 2017, to October 6, 2023, using visible network graphs, covering 34 provincial-level administrative regions in China. Firstly, a literature review is conducted to provide a theoretical foundation for subsequent analysis. Then, the paper elaborates on the basic concepts of complex networks, parameters, and the principles of visible network graph algorithms. On this basis, the application of system clustering and community detection algorithms is explored. The paper also conducts a detailed empirical analysis of the collected data, starting with an analysis of data for various provinces in China, including the construction of visible network graphs, the study of scale-free networks, and discussions on regional system clustering. Subsequently, a nationwide analysis of data is performed, with a focus on the construction of visible network graphs for the visibility of professional competency awareness and the study of community structures. Through this study, a deeper understanding of the awareness of professional competency in different regions can be obtained, providing valuable references for policy formulation and corporate decision-making.